2015
DOI: 10.1097/nor.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multifactorial Intervention Programs on Health Behavior and Symptom Control Among Community-Dwelling Overweight Older Adults With Knee Osteoarthritis

Abstract: The MUFIPs can break down the progression of the disease among overweight older Thais with knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 13 publications
0
48
0
1
Order By: Relevance
“…No further studies were found by checking reference lists. Twenty quantitative publications and two qualitative publications were excluded at this stage. Excluded publications are listed with reasons for exclusion (SI4).…”
Section: Resultsmentioning
confidence: 99%
“…No further studies were found by checking reference lists. Twenty quantitative publications and two qualitative publications were excluded at this stage. Excluded publications are listed with reasons for exclusion (SI4).…”
Section: Resultsmentioning
confidence: 99%
“…Sisettakul & Kongtaln (2017) focused on dementia screening and community care management. Other studies described strengthening social participation by integrating community capacity for a home‐based exercise and visit programme (Robrujen et al 2018; Saraboon et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…This approach was evident in examining specific health needs and cost‐effectiveness. Six studies evaluated patient needs outside routine clinic hours; intervention visits decreased unnecessary ED visits, assisted caregivers and lifestyle integration (Kant et al 2018; Ritchie et al 2016; Robrujen et al 2018; Ruedej et al 2018; Saraboon et al 2015; Wiriyasombat et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies found that home visitation was a significant predictor of life-quality improvement for knee OA. 22 , 23 …”
Section: Discussionmentioning
confidence: 99%